Corneal Collagen Cross-Linking in Pediatric Patients: Ten Year Experience - Félix, Raquel (2022)
INTRODUCTION: Keratoconus (KC) is a corneal ectatic disorder characterized by pro- gressive corneal thinning and steepening. Corneal collagen cross-linking (CXL) uses riboflavin and ultraviolet-A radiation to induce cross-links in the stromal collagen, increasing its biomechanical rigidity and halting the progression of KC. Different protocols of CXL have been proposed throughout the years to improve clinical results and patient comfort. However, management of pediatric cases remains particularly challenging because younger patients tend to exhibit a more rapid progression of the disease. In this study we aim to evaluate the efficacy of CXL in a population of pediatric patients aged 18 years or less with progressive KC. MATERIAL AND METHODS: Multi-center, retrospective, cross-sectional study. Patients with progressive KC, aged ≤ 18, who underwent CXL between 2010 and 2021 were reviewed. Different modalities of CXL were used: Standard CXL, Accelerated CXL, Combined CXL and partial topography-guided PRK (photorefractive keratectomy), and Customized CXL. Evaluation included best spectacle corrected visual acuity (BSCVA), manifest refraction, and Scheimpflugtomography evaluation. Baseline and follow-up values were compared. RESULTS AND DISCUSSION: The study included 44 eyes of 33 patients, 26 (78.8%) male and 7 (21.2%) female. Mean age at time of CXL was 15.2±3.1 years [range 10-18]. Convention- al CXL was performed in 9 eyes, and accelerated CXL in 14 eyes. Seven eyes performed combined CXL and simultaneous topography guided PRK. Fourteen eyes performed customized irradiation CXL. Epithelium was removed before CXL in all patients. Mean follow-up was 21.9±16.6 months [range 4-66]. At the last follow-up, mean BSCVA was improved from 0.43±0.26 to 0.38±0.25 Log- MAR (p=0.067). Preoperative mean spherical equivalent increased from -1.97±2.44 to -2.41±3.60 D (p=0.509) and cylinder decreased from 2.85±1.92 to 2.34±1.77 D (p=0.045). The flat keratometric values (K1) remained stable, from 48.04±4.87 to 48.74±5.12 D (p=0.358), as well as the steep keratometric values (K2), from 53.63±6.60 to 53.98±6.09 D (p=0.721), and maximum keratometry values (K max), from 62.45±10.38 to 62.20±10.01 D (p=0.764). Thinnest corneal thickness decreased from 452.03±39.63 to 423.59±43.17 μm (p<0.001). Mean spherical equivalent increased in conventional CXL eyes, and had a greater decrease in those having undergone combined CXL and PRK (p=0.042). Thinnest corneal thickness decreased more significantly in the combined CXL and PRK eyes (p<0.001). No other differences between different CXL protocols were significant. Success rate at the last follow-up was 90.9%, with 4 eyes (9.1%) showing progression after CXL: 2 following accelerated CXL and 2 following customized irradiation CXL. CONCLUSION: CXL seems to halt the progression of KC in pediatric patients and result in stabilization of visual acuity and topographic parameters. Our results are in line with the published international series for pediatric KC, showing overall good results but more risk of progression than adult patients. Alternative protocols seem to be equally effective as standard-CXL in pediatric KC.